(3GdRjHbs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3agPG gh GdcJGH GdSGOS GdefShH dYWGQO GdcGJH ef LedI GdLRA GdQGHY ef cJGH GdHQgGf ai CSQGQ Yde GdReGf s
(3BNQgG (B:s
(3aGage Pdc hGYed HMSHg JQTjO Ef TGA Gddg JYGdi hcGf ai HbjI GdcJGH C(B'(3eGd WhjdI JQcfGgG YeOkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B232 - (3U(B233s
(3GdfSNI HgG MhGTs
(3hgh GdcJGH GdSOGS ef cJGH GdHQgGf ai CSQGQ Yde GdejRGfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs